О влиянии огибающей излучаемого радиоимпульса на оценки плазменных температур, определяемых с помощью метода некогерентного рассеяния - Котов, Дмитрий Владимирович; Богомаз, Александр Викторович; Лялюк, А. И.; Искра, Д. А. (НТУ "ХПИ", 2014)
Рассмотрено влияние формы огибающей зондирующего импульса на результаты решения обратной задачи радиофизики (оценка параметров ионосферной плазмы с помощью метода некогерентного рассеяния). Показано, что использование измеренной по разработанному алгоритму огибающей зондирующего радиоимпульса привело к существенному улучшению результатов решения обратной задачи радиофизики. Устранены систематические погрешности оценивания параметров ионосферы, которые возникали вследствие неучѐта реальной формы огибающей импульса.

The influence of the shape of sounding pulse envelope on the results of inverse radiophysical problem solving (estimation of parameters of ionosphere plasma by means of in incoherent scatter technique) is studied. It is shown that involving of real pulse en velope into the calculation of radar ambiguity function led to significantly better results of inverse radiophysical problem solving. Real pulse envelope was obtained by means of the developed algorithm based on using the external antenna and the precision high-speed analog-to-digital converter. Systematic biases in estimated parameters of ionosphere were eliminated. Values of biases in ionosphere plasma temperature for different physical conditions are obtained.
Towards the influence of the envelope of the transmitted radio pulse on the estimated plasma temperature obtained by using the incoherent scattering technique
Keywords: функция неопределѐнности; огибающая импульса; зондирующая импульса; радиофизика; incoherent scatter radar; ambiguity function; pulse envelope